Kemampuan Berpikir Kreatif Peserta Didik pada Materi Fluida Statis Menggunakan Model Problem Based Learning (PBL) - Dewi Fitriana Dewi; Nurul Septiana; Nur Inayah Syar (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2023)
This research is based on the results of initial observations and interviews, it was found that students were less enthusiastic about physics lessons. The learning process that occurs in the teacher's classroom is more dominant than the students. This causes students to be less motivated to be more active in the learning process and less involved in the learning process. In addition, the results of interviews with students who were only presented with practice questions and more listening to material explanations could lead to a lack of interaction between teachers and students in the learning process. The teacher also has never applied a problem-based learning model when teaching static fluid material. This study aims to describe students' creative thinking skills in static fluid material using the Problem Based Learning (PBL) model at SMAN 2 Kuala Pemburan. This research uses the type of experimental research. The research was carried out in class XI MIPA SMAN 2 Kuala Pemburan in the odd semester which was conducted in July on the subject matter of Static Fluids for the 2021/2022 teachings. The instruments used are in the form of test questions about creative thinking skills, lesson plans (RPP), student worksheets, and observation sheets. The population used was students of class XI MIPA at SMAN 2 Kuala Pembuang.